2015
DOI: 10.15430/jcp.2015.20.3.216
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Grading of Oral Submucous Fibrosis With Frequency and Consumption of Areca Nut and Its Derivatives in a Wide Age Group: A Multi-centric Cross Sectional Study From Karachi, Pakistan

Abstract: Background:Oral submucous fibrosis (OSMF) is a chronic, premalignant condition of the oral mucosa and one of the commonest potentially malignant disorders amongst the Asian population. The objective of this study was to investigate the association of etiologic factors with: age, frequency, duration of consumption of areca nut and its derivatives, and the severity of clinical manifestations.Methods:A cross-sectional, multi centric study was conducted over 8 years on clinically diagnosed OSMF cases (n = 765) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 18 publications
3
23
0
Order By: Relevance
“…In this study, no significant deviation was observed in the distribution of the participants according to age and gender based on the OSMF grading. This finding was in accordance to the study conducted by Hosein et al .,[8] where they found similar findings. The clinical and functional grading of OSMF was adopted from Haider et al .…”
Section: Discussionsupporting
confidence: 94%
“…In this study, no significant deviation was observed in the distribution of the participants according to age and gender based on the OSMF grading. This finding was in accordance to the study conducted by Hosein et al .,[8] where they found similar findings. The clinical and functional grading of OSMF was adopted from Haider et al .…”
Section: Discussionsupporting
confidence: 94%
“…In fact, current investigations indicated that the most serious side-effects of arecoline are the oral toxicities Chen et al 2014). Oral submucous fibrosis (OSF) is a potentially malignant disease predominantly seen in people of Asian; epidemiological surveys provide valid evidence that chewing AN can lead to OSF, and arecoline is the main etiological factor (Prabhu et al 2014;Hosein et al 2015). It could interfere with the molecular processes of deposition and/or degradation of extracellular matrix (ECM) molecules, such as collagen, causing imbalance in the normal process (Utsunomiya et al 2005;Tilakaratne et al 2006;Arakeri & Brennan 2013).…”
Section: Toxicologymentioning
confidence: 99%
“…Chronic usage of areca nut will lead to infectious lesions that lead to various oral disorders and could transform to oral carcinogenesis, collectively called as orally potential malignant disorders (OPMDs) [ 14 , 15 ]. Areca alkaloid arecoline is a significant etiological factor that is responsible to cause cytotoxicity and genotoxicity in various cell system [ 16 , 17 ]. Various active constituents of areca nut extract have been reported to cause decreased viability with increased generation of free radicals [ 18 ].…”
Section: Introductionmentioning
confidence: 99%